A facile method for bright, colour-tunable light-emitting diodes based on Ga-doped ZnO nanorods - Rahman, M Azizar; Scott, John A; Gentle, A; Phillips, Matthew R; Ton-That, Cuong (Nanotechnology, 2018)
Bottom-up fabrication of nanowire-based devices is highly attractive for oxide photonic devices because of high light extraction efficiency; however, unsatisfactory electrical injection into ZnO and poor carrier transport properties of nanowires severely limit their practical applications. Here, we demonstrate that ZnO nanorods doped with Ga donors by in situ dopant incorporation during vapour-solid growth exhibit superior optoelectronic properties that exceed those currently synthesised by chemical vapour deposition, and accordingly can be electrically integrated into Si-based photonic devices. Significantly, the doping method was found to improve the nanorod quality by decreasing the concentration of point defects. Light-emitting diodes (LEDs) fabricated from the Ga-doped ZnO nanorod/p-Si heterojunction display bright and colour-tunable electroluminescence (EL). These nanorod LEDs possess a dramatically enhanced performance and an order of magnitude higher EL compared with equivalent devices fabricated with undoped nanorods. These results point to an effective route for large-scale fabrication of conductive, single-crystalline ZnO nanorods for photonic and optoelectronic applications.